2021
DOI: 10.3390/en14040964
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Up Performance of Catalyst Carriers—A Parameter Study and Thermodynamic Analysis

Abstract: This study investigates geometric parameters of commercially available or recently published models of catalyst substrates for passenger vehicles and provides a numerical evaluation of their influence on heat-up behavior. Parameters considered to have a significant impact on the thermal economy of a monolith are: internal surface area, heat transfer coefficient, and mass of the converter, as well as its heat capacity. During simulation experiments, it could be determined that the primary role is played by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…The front views in Figure 3 show that the streamlines are distributed better in the octet and P-TPMS structures than in the other structures. The flow is classified as turbulent based on the Reynolds number of 2300 [20]. Thus, the results confirmed that only octet, Kelvin, and P-TPMS structures caused turbulent flow, with the maximum (c,d,g,h) velocity distributions for the different 3D microstructures; (e,f,i,j) front view of fluid flow distributions.…”
Section: Velocity Distributionsupporting
confidence: 58%
See 1 more Smart Citation
“…The front views in Figure 3 show that the streamlines are distributed better in the octet and P-TPMS structures than in the other structures. The flow is classified as turbulent based on the Reynolds number of 2300 [20]. Thus, the results confirmed that only octet, Kelvin, and P-TPMS structures caused turbulent flow, with the maximum (c,d,g,h) velocity distributions for the different 3D microstructures; (e,f,i,j) front view of fluid flow distributions.…”
Section: Velocity Distributionsupporting
confidence: 58%
“…By utilizing porous penetrating structures such as FCC and SC structures, it is possible to induce an inertial flow and improve the mass transfer [19]. A high geometric surface area and low heat capacity are required in the design of the catalytic carrier to improve the performance of catalytic converter systems [20]. There is a scarcity of reports confirming the substitutability and performance of existing monolithic structures by application of a fine lattice structure to catalytic transducers.…”
Section: Introductionmentioning
confidence: 99%
“…The most efficient part of the emission system is the three-way catalyst, which works under optimum conditions with an efficiency of up to 98%. The aim is, therefore, to stabilize the conditions in the exhaust pipe [24].…”
Section: Aftertreatment Systemmentioning
confidence: 99%